WEBVTT
00:00:02.520 --> 00:00:10.760
In this lesson on orbital speed, weโre going to learn how to relate the orbital speed of an object to information about the gravitational attraction between the object and the body itโs orbiting.
00:00:11.280 --> 00:00:17.720
For an object moving along a circular path, the velocity of the object always points tangent to the path.
00:00:18.440 --> 00:00:22.280
And this is true no matter where on the circle the object is located.
00:00:22.840 --> 00:00:28.360
The reason the velocity is always tangent to the path is because the velocity points in the direction of motion.
00:00:28.880 --> 00:00:38.760
And if we zoom in at any given time on the portion of the path where the object is located, the path will more and more closely resemble the line tangent to the path at that point.
00:00:39.200 --> 00:00:43.760
So, at any given moment, the motion of the object appears to be along the line tangent to the path.
00:00:44.120 --> 00:00:46.880
So, the velocity points tangent to the path at each point.
00:00:47.360 --> 00:00:51.320
Weโre going to be interested in objects that have a constant speed as they move around the circle.
00:00:51.800 --> 00:00:55.680
This means that the size of the velocity vectors is the same at every point.
00:00:56.120 --> 00:01:00.960
However, as we can clearly see from the picture, the direction of the velocity changes.
00:01:01.440 --> 00:01:05.080
But if an objectโs velocity changes direction, the object is accelerating.
00:01:05.640 --> 00:01:08.200
We call this acceleration centripetal acceleration.
00:01:08.640 --> 00:01:18.920
As a formula, we can write ๐ c, the centripetal acceleration, is equal to ๐ฃ squared over ๐, where ๐ฃ is the speed of the object and ๐ is the radius of the circular path.
00:01:19.560 --> 00:01:23.120
This expression gives us the magnitude of the centripetal acceleration.
00:01:23.120 --> 00:01:27.800
The direction of the centripetal acceleration will be radially inward towards the center of the circle.
00:01:28.280 --> 00:01:38.720
Visually, we can see that this is the correct direction because in order to keep the velocity vector tangent to the circle at each point, we must continually move the head of the vector in towards the center of the circle.
00:01:39.720 --> 00:01:41.360
Now, letโs recall the Newton second law.
00:01:41.600 --> 00:01:51.600
It tells us that an accelerating object with a mass of ๐ will be experiencing a force whose size is the mass times the acceleration and the direction is the same as the acceleration.
00:01:52.200 --> 00:02:01.960
In other words, in order for our mass to stay on the circular path, it must be constantly experiencing a centripetal force which has the same direction as the centripetal acceleration.
00:02:02.600 --> 00:02:06.760
Letโs now bring this discussion to the specific case of circular orbits that weโre interested in.
00:02:07.480 --> 00:02:13.280
In order for our object to stay in orbit around a planet, there needs to be some source of centripetal force.
00:02:13.560 --> 00:02:18.840
Well, in a situation like this, there is one force that acts radially inward between the planet and the object.
00:02:19.160 --> 00:02:20.280
And thatโs the force of gravity.
00:02:20.880 --> 00:02:23.200
The direction of the gravitational force is radially inward.
00:02:23.760 --> 00:02:35.400
The size of the gravitational force in terms of the mass of the planet, capital ๐, the mass of the object, lowercase ๐, and the radius, ๐, measured from the center of the planet to the orbital path is given by.
00:02:35.800 --> 00:02:43.080
๐บ, the universal gravitational constant, times the mass of the planet times the mass of the object divided by the distance between them squared.
00:02:43.600 --> 00:02:51.360
The distance between them is the same as the orbital radius, since at every point along the path, the object will be ๐ away from the center of the planet.
00:02:51.800 --> 00:02:56.560
Note that when we say the center of the planet or the center of the object, we mean their centers of gravity.
00:02:57.200 --> 00:03:04.040
Our stated goal was to relate the orbital speed of the object to information about the gravitational attraction between the object and the planet.
00:03:04.640 --> 00:03:14.680
The last observation we need before we derive a formula is that the gravitational attraction between the planet and the object is providing the centripetal force on the object to keep it on its path.
00:03:15.320 --> 00:03:21.160
We can, therefore, write ๐น c, the centripetal force, is equal to ๐น g, the gravitational force.
00:03:21.480 --> 00:03:24.480
Letโs now plug in the relevant information from our three formulas.
00:03:24.800 --> 00:03:28.960
By Newtonโs second law, the centripetal force is mass times the centripetal acceleration.
00:03:29.480 --> 00:03:38.640
By using ๐ฃ squared over ๐ as the definition of centripetal acceleration, we can write mass times centripetal acceleration as mass times orbital speed squared over orbital radius.
00:03:38.920 --> 00:03:43.680
On the other side of the equation, gravitational force is just given by the expression we mentioned before.
00:03:44.160 --> 00:03:55.880
Okay, now, weโre really close to our goal because we have a term on the left-hand side of the equation with the orbital speed which weโre looking for and the right-hand side of the equation is information about the gravitational attraction between the two bodies.
00:03:56.360 --> 00:03:59.960
Weโll start by noting that thereโs a factor of lowercase ๐ on both sides of the equation.
00:04:00.440 --> 00:04:04.440
Thereโs also at least one factor of ๐ in the denominator on both sides.
00:04:04.840 --> 00:04:07.600
So, letโs multiply both sides by ๐ over lowercase ๐.
00:04:08.120 --> 00:04:13.000
On both the left-hand side and the right-hand side, we have ๐ divided by ๐, which is just one.
00:04:13.600 --> 00:04:16.360
On the left-hand side, ๐ divided by ๐ is one.
00:04:16.680 --> 00:04:20.320
And on the right-hand side, ๐ divided by ๐ squared is just one over ๐.
00:04:20.840 --> 00:04:29.160
This leaves us with speed squared on the left-hand side and universal gravitational constant times mass of the planet divided by the orbital radius on the right-hand side.
00:04:29.640 --> 00:04:32.920
Our final step will be to take the square root of both sides of this equation.
00:04:33.200 --> 00:04:36.160
The square root of orbital speed squared is just orbital speed.
00:04:36.600 --> 00:04:41.120
And the right-hand side is just as it was before, square root of ๐บ capital ๐ over ๐.
00:04:41.600 --> 00:04:46.760
We have thus succeeded in finding a formula for the orbital speed of an object in a circular orbit.
00:04:47.240 --> 00:04:53.680
In terms of the universal gravitational constant, the mass of the body that our object is orbiting, and the radius of the orbit.
00:04:54.200 --> 00:05:00.920
Itโs worth stressing again that this formula only applies in the special case of a circular orbit where the orbital speed is constant.
00:05:01.440 --> 00:05:06.280
If the orbit is not a circle, the orbital speed will not be constant and this formula will not apply.
00:05:06.960 --> 00:05:11.480
Note also that lowercase ๐, the mass of our object, does not appear in this formula.
00:05:12.000 --> 00:05:22.840
What this means is that all objects, no matter what their mass is, that are moving in circular orbits with the same orbital radius around planets with the same mass will all have the same orbital speed.
00:05:23.480 --> 00:05:32.360
As weโve written it, this equation allows us to find the orbital speed, but we can also rearrange this equation to find the mass of the planet and the radius of the orbit.
00:05:32.880 --> 00:05:34.640
Weโll start by squaring both sides.
00:05:35.000 --> 00:05:39.000
This gives us back our previous equation ๐ฃ squared equals ๐บ๐ over ๐.
00:05:39.520 --> 00:05:42.600
To solve for ๐, we multiply both sides by ๐ over ๐ฃ squared.
00:05:43.040 --> 00:05:48.240
On the left-hand side, ๐ over ๐ฃ squared times ๐ฃ squared is just ๐, which is what we were looking for.
00:05:48.760 --> 00:05:55.560
And on the right-hand side, ๐ in the numerator divided by ๐ in the denominator is just one and weโre left with ๐บ๐ over ๐ฃ squared.
00:05:56.080 --> 00:06:00.680
In this form, we have orbital radius in terms of mass of the planet and orbital speed.
00:06:01.000 --> 00:06:12.080
If we multiply both sides of our previous equation by ๐ over ๐บ instead of ๐ over ๐ฃ squared, then on the right-hand side ๐ over ๐บ times ๐บ over ๐ is one.
00:06:12.680 --> 00:06:16.320
And weโre left with just the mass of the planet which weโll put on the left-hand side of our final result, just to keep consistency.
00:06:16.880 --> 00:06:19.840
And on the left-hand side, we have ๐ times ๐ฃ squared over ๐บ.
00:06:20.360 --> 00:06:25.680
And that leaves us with ๐ is equal to ๐๐ฃ squared over ๐บ.
00:06:26.000 --> 00:06:36.760
So, with these three equations, we can find the orbital speed or the orbital radius or the mass of the planet as long as we know a value for the universal gravitational constant and also have values for the other two quantities.
00:06:37.160 --> 00:06:42.040
Before moving on to a few examples of how to apply these equations, letโs see one more way to write them.
00:06:42.480 --> 00:06:52.600
If we solve any of these equations for ๐บ, we find the universal gravitational constant is equal to the orbital radius times the orbital speed squared divided by the mass of the planet.
00:06:53.080 --> 00:07:01.400
What this means is that if we could independently measure the orbital radius and orbital speed of a circular orbit around a planet and could also measure that planetโs mass.
00:07:01.720 --> 00:07:07.680
We could find a value for the universal gravitational constant that we could then use every other time gravity comes into play.
00:07:08.240 --> 00:07:15.920
We could also test the validity of our theory of gravity by comparing this measure of the universal gravitational constant to other measures of the universal gravitational constant.
00:07:16.720 --> 00:07:20.840
Anyway, letโs now see some examples of how to apply the formulas weโve just derived.
00:07:21.920 --> 00:07:28.000
For a satellite to follow a circular orbit around Earth at a radius of 10,000 kilometers, what orbital speed must it have?
00:07:28.600 --> 00:07:40.560
Use a value of 5.97 times 10 to 24th kilograms for the mass of Earth and 6.67 times 10 to the negative 11th meters cubed per kilogram per second squared for the value of the universal gravitational constant.
00:07:40.960 --> 00:07:43.000
Give your answer to three significant figures.
00:07:43.280 --> 00:07:48.400
Okay, so hereโs the Earth with a mass of 5.97 times 10 to 24th kilograms.
00:07:48.880 --> 00:07:53.760
And here is the circular orbit with a radius of 10,000 kilometers, as measured from the center of the Earth.
00:07:54.360 --> 00:07:58.080
Finally, hereโs a satellite moving along the orbit with an unknown speed.
00:07:58.720 --> 00:08:06.840
For the satellite to maintain a constant circular orbit, it must be experiencing a centripetal force which comes from the force of gravity that the Earth exerts on the satellite.
00:08:07.280 --> 00:08:11.800
Letโs call the mass of the satellite lowercase ๐, which is not a quantity that weโre given in the problem.
00:08:12.400 --> 00:08:18.800
Using lowercase ๐, ๐ฃ, ๐, capital ๐, and the universal gravitational constant.
00:08:19.080 --> 00:08:27.280
We can write ๐น c, the centripetal force, is equal to the mass of the satellite times the square of the orbital speed divided by the orbital radius.
00:08:27.640 --> 00:08:40.320
Also, ๐น g, the force of gravity that Earth exerts on the satellite, is equal to the universal gravitational constant given the symbol capital ๐บ times the mass of Earth times the mass of the satellite divided by the square of the orbital radius.
00:08:40.720 --> 00:08:47.760
Since the centripetal force is provided by the gravitational force, we can equate these two quantities and then solve for the orbital speed.
00:08:48.240 --> 00:08:56.400
We get ๐ฃ is equal to the square root of ๐บ times capital ๐ divided by ๐, whereas we can see the mass of the satellite does not appear in this final expression.
00:08:56.960 --> 00:09:00.000
In our question, weโre given a value for the universal gravitational constant.
00:09:00.520 --> 00:09:07.440
So combining that with our known values for orbital radius and mass of Earth, we should be able to plug in to get a value for the orbital speed.
00:09:08.120 --> 00:09:23.080
When we actually put in those numbers, we find that ๐ฃ is equal to the square root of 6.67 times 10 to the negative 11th meters cubed per kilogram per second squared times 5.97 times 10 to the 24th kilograms divided by 10,000 kilometers.
00:09:23.520 --> 00:09:26.280
Letโs start with two simplifications involving the units.
00:09:26.840 --> 00:09:30.400
We have a factor of per kilograms and a factor of kilograms.
00:09:30.720 --> 00:09:32.880
And per kilograms times kilograms is just one.
00:09:33.400 --> 00:09:39.640
Second, weโll need to convert kilometers to meters in the denominator to match the meters already present in the numerator.
00:09:40.280 --> 00:09:44.200
Recall that one kilometer is by definition 1000 meters.
00:09:44.480 --> 00:09:53.240
So, 10,000 kilometers is 10,000 times 1000 meters or, converting to scientific notation, 10 to the seventh meters.
00:09:53.640 --> 00:09:58.440
Finally, meters cubed in the numerator divided by meters in the denominator is meters squared.
00:09:58.920 --> 00:10:04.000
Letโs rewrite this expression separating the numbers, the powers of 10, and the units.
00:10:04.480 --> 00:10:17.080
Written out like this, using the commutativity and associativity of multiplication, we can now calculate the value of each of these terms separately, take the square roots separately, and multiply all those together to get the final result.
00:10:17.600 --> 00:10:18.760
Letโs start with the units.
00:10:19.040 --> 00:10:22.360
Meters squared per second squared is meters per second squared.
00:10:22.960 --> 00:10:26.720
Moving on to the powers of 10, our final result will have a base of 10.
00:10:27.080 --> 00:10:32.120
And to get the exponent, we add the exponents in the numerator and subtract the exponents in the denominator.
00:10:32.960 --> 00:10:37.520
Negative 11 plus 24 is 13 minus seven is six.
00:10:37.920 --> 00:10:40.600
So, that whole term reduces to 10 to the sixth.
00:10:41.240 --> 00:10:47.120
Finally, 6.67 times 5.97 is equal to 39.8199.
00:10:47.600 --> 00:10:54.920
To finish the calculation, we recall that the square root of a product of several terms is equal to the product of the square root of those terms.
00:10:55.360 --> 00:11:03.440
So, we have that ๐ฃ is equal to the square root of 39.8199 times the square of 10 to the sixth times the square root of meters per second squared.
00:11:04.040 --> 00:11:06.000
Okay, so letโs work out these square roots.
00:11:06.280 --> 00:11:10.000
To take the square root of a squared quantity, well, thatโs just the quantity itself.
00:11:10.680 --> 00:11:14.000
So, the square root of meters per second squared is just meters per second.
00:11:14.640 --> 00:11:18.480
This is a good intermediate result because meters per second is a unit of speed.
00:11:18.760 --> 00:11:22.720
So, we see that weโre looking for a speed, and our final answer will have units of speed.
00:11:23.240 --> 00:11:28.040
In general, to take the square root of any quantity raised to a power, simply halve the power.
00:11:28.440 --> 00:11:30.880
So, the square root of 10 to the sixth is 10 to the third.
00:11:31.520 --> 00:11:34.680
Lastly, we have the square root of 39.8199.
00:11:35.160 --> 00:11:36.680
For this, we just need a calculator.
00:11:37.200 --> 00:11:41.640
The first several digits of that result are 6.3103 et cetera.
00:11:42.200 --> 00:11:50.680
Now, we have our answer as a number times the power of 10 times some units, which is a very useful form for expressing it to three significant figures.
00:11:51.160 --> 00:11:59.360
To express our answer this way, we simply need to find the three significant figures of the number portion and then carry the power of 10 and the units to the final answer.
00:11:59.920 --> 00:12:08.120
To identify some number of significant figures, we count that many digits, starting from the first nonzero digit and going left to right.
00:12:08.760 --> 00:12:13.200
For our number, the first significant figure is six and the second is three.
00:12:13.840 --> 00:12:18.520
To find the third significant figure, since thatโs the last one that weโre looking for, we have to round.
00:12:19.080 --> 00:12:21.000
So, we look at the fourth digit, which is zero.
00:12:21.560 --> 00:12:24.920
And since zero is less than five, one rounds to one.
00:12:25.480 --> 00:12:29.280
So, our number to three significant figures is 6.31.
00:12:29.880 --> 00:12:31.760
Now, letโs just finish out the multiplication.
00:12:32.160 --> 00:12:44.360
6.31 times 10 to the third is 6,310 times meters per second gives us a final answer of 6,310 meters per second to three significant figures.
00:12:44.720 --> 00:12:51.840
And this is the orbital speed that a satellite would need to maintain to have a circular orbit around Earth with a radius of 10,000 kilometers.
00:12:52.920 --> 00:12:55.200
This example was very focused on calculations.
00:12:55.520 --> 00:13:01.120
Letโs now see an example thatโs focused on the qualitative relationship between orbital speed and orbital radius.
00:13:02.000 --> 00:13:09.200
Which line on the graph shows the relation between orbital speed and orbital radius for objects moving along circular orbits due to gravity?
00:13:09.720 --> 00:13:21.800
The question asks us to identify which of the curves on this graph, which has orbital radius on the horizontal axis and orbital speed on the vertical axis, corresponds to the correct functional relationship between those two quantities.
00:13:22.120 --> 00:13:26.960
Recall that by equating the centripetal force and the gravitational force for an object in a circular orbit.
00:13:27.280 --> 00:13:36.640
We find that the orbital speed is equal to the square root of the universal gravitation constant times the mass of the body being orbited divided by the radius of the orbit.
00:13:37.240 --> 00:13:47.320
Since our question is only about the relationship between orbital speed and orbital radius, we can treat the mass of the body being orbited, that is capital ๐, as constant.
00:13:47.520 --> 00:14:01.120
Then, since capital ๐บ is also constant, we can rewrite our formula as orbital speed is equal to the square root of a constant divided by the orbital radius, where weโve used the fact that a constant times a constant is just another constant.
00:14:01.720 --> 00:14:11.640
Now, using the fact that the square root of a constant is just another constant, we can rewrite this form as orbital speed is equal to a constant divided by the square root of the orbital radius.
00:14:12.080 --> 00:14:14.320
We donโt actually care about the identity of this constant.
00:14:14.760 --> 00:14:19.080
So, we can rewrite this equation as a qualitative proportionality relationship.
00:14:19.680 --> 00:14:23.760
And that relationship is that ๐ฃ is proportional to one over the square root of ๐.
00:14:24.240 --> 00:14:33.800
Weโve written the relationship this way to focus on the connection between orbital speed and orbital radius and avoid getting confused by constants that are not relevant to this particular question.
00:14:34.320 --> 00:14:45.880
Letโs now use this functional form to make predictions for the orbital speed corresponding to large orbital radii, that is the right edge of the graph, and to small orbital radii, that is the left edge of the graph.
00:14:46.680 --> 00:14:49.200
We can then match those predictions to the appropriate line.
00:14:49.640 --> 00:14:51.880
Letโs see what happens as ๐ increases.
00:14:52.200 --> 00:14:56.440
As the orbital radius gets larger, the square root of the orbital radius also gets larger.
00:14:56.800 --> 00:15:04.440
So one over the square root of the orbital radius gets smaller because as the denominator of a fraction grows, the size of the fraction shrinks.
00:15:04.840 --> 00:15:08.520
So when orbital radius increases, we expect orbital speed to decrease.
00:15:08.880 --> 00:15:14.040
Although because orbital radius can never be infinite, the orbital speed can never be zero.
00:15:14.440 --> 00:15:21.680
Looking at the graph, clearly, the green line doesnโt work because it never changes, so it isnโt decreasing with increasing radius.
00:15:22.000 --> 00:15:25.920
The blue, orange, and red lines all decrease with increasing radius.
00:15:26.320 --> 00:15:30.160
But it also canโt be the red line because the red line reaches zero.
00:15:30.160 --> 00:15:32.480
And we know that the orbital speed can never be zero.
00:15:33.000 --> 00:15:35.760
Letโs now see what happens as the orbital radius shrinks.
00:15:36.320 --> 00:15:39.240
As ๐ decreases, so does the square root of ๐.
00:15:39.640 --> 00:15:42.120
So, the denominator of our fraction is shrinking.
00:15:42.560 --> 00:15:44.520
And so, the fraction itself is growing.
00:15:45.000 --> 00:15:49.240
And since the fraction is proportional to orbital speed, the orbital speed is also growing.
00:15:49.840 --> 00:15:56.160
We also know that as the denominator of a fraction gets closer and closer to zero, the value of that fraction increases without limit.
00:15:56.760 --> 00:16:02.240
So here, too, we expect the orbital speed to increase without limit as the orbital radius gets closer to zero.
00:16:02.720 --> 00:16:06.000
The orange curve has a maximum value as the radius approaches zero.
00:16:06.400 --> 00:16:10.400
So, the orange curve is not the right curve because the orbital speed doesnโt increase without limit.
00:16:10.920 --> 00:16:13.080
This leaves the blue line as the correct answer.
00:16:13.400 --> 00:16:22.280
Indeed, the blue line shows an orbital speed that gets smaller and smaller as the radius increases and gets larger and larger without limit as the radius decreases.
00:16:22.280 --> 00:16:30.200
So, the answer is that the blue line shows the correct relationship between orbital speed and orbital radius for objects moving in circular orbits due to gravity.
00:16:31.560 --> 00:16:35.400
Now that weโve seen some examples, letโs summarize the key points that weโve learned in this lesson.
00:16:35.880 --> 00:16:39.880
We can find our discussion to circular orbits caused by gravitational fields.
00:16:40.200 --> 00:16:47.720
In such a case, we found that we could equate the centripetal force, keeping the object moving in a circle, to the gravitational force acting on the object.
00:16:48.200 --> 00:16:53.400
Using the definition of centripetal force as mass of the object times speed squared divided by the radius.
00:16:53.680 --> 00:17:02.560
And the definition of gravitational force as the universal gravitational constant times the mass of the planet times the mass of the orbiting object divided by radius squared.
00:17:03.000 --> 00:17:13.440
We derive the equation for the orbital speed as ๐ฃ is equal to the square root of the universal gravitational constant, ๐บ, times the mass of the planet, capital ๐, divided by the orbital radius, ๐.
00:17:14.160 --> 00:17:18.040
We then solve this equation for ๐ and ๐ to get two more formulas.
00:17:18.600 --> 00:17:29.320
We found that the orbital radius is equal to ๐บ times the mass of the planet divided by the orbital speed squared and that the mass of the planet is equal to the orbital radius times the orbital speed squared divided by ๐บ.
00:17:29.920 --> 00:17:38.960
Finally, we noted that given an appropriate value, for ๐บ, we could find orbital speed, orbital radius, or mass of the planet from values of the other two quantities.